2005
DOI: 10.1207/s15327019eb1501_3
|View full text |Cite
|
Sign up to set email alerts
|

How Informed Is Online Informed Consent?

Abstract: We examined participants' reading and recall of informed consent documents presented via paper or computer. Within each presentation medium, we presented the document as a continuous or paginated document to simulate common computer and paper presentation formats. Participants took slightly longer to read paginated and computer informed consent documents and recalled slightly more information from the paginated documents. We concluded that obtaining informed consent online is not substantially different than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 16 publications
2
81
0
2
Order By: Relevance
“…Varnhagen et al (2005) found that e-mail consent increased the amount participants remembered but was otherwise no different from paper-and-pencil consent. E-mailed surveys are increasingly being used for data collection in studies reported in peerreviewed journals (e.g., Calder et al, 2004 andEllett et al, 2005).…”
Section: Limitationsmentioning
confidence: 84%
“…Varnhagen et al (2005) found that e-mail consent increased the amount participants remembered but was otherwise no different from paper-and-pencil consent. E-mailed surveys are increasingly being used for data collection in studies reported in peerreviewed journals (e.g., Calder et al, 2004 andEllett et al, 2005).…”
Section: Limitationsmentioning
confidence: 84%
“…Participants were given online instructions and completed each week’s session from the convenience of their home computer. At week 1 (recruitment), participants were recruited by an online agency, signed an online consent form [25], and completed an online questionnaire on their current saturated fat intake, risk perceptions, self-efficacy, and intentions to change their dietary intake. They also received educational information on the importance of a healthy diet low in saturated fat (Multimedia Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…All subjects gave online informed consent in accordance with the Declaration of Helsinki. It was not possible to obtain written informed consent, as both studies were conducted solely via the Internet, yet online informed consent was shown to be similar to written informed consent (see Varnhagen et al, 2005). The protocol was exempt from approval as stated by the guidelines of the ethics committee of the Faculty of Arts at the University of Zurich, as it passed a checklist of ethical innocuousness (which serves as ethical approval in accordance with the local guidelines).…”
Section: Ethics Statementmentioning
confidence: 99%